مقارنة سموك االحتجاز لمركبات االلديهايد والكيتون باستعمال البمورات السائمة كطور ثابت مع االعمدة التقميدية في كروماتوغرافيا الغاز – سائل - عبدالله زينب محمود; عباس ثائر ارحيل; وادي امل ناجي; حمزة فيحاء ميسر; دحام هادي كريم (Al-Nahrain Journal of Science, 2011)
Abstract: The objective goal of this research was concentrated on the study of chromatographic behavior Aldehyde and Ketone compounds on two different stationary phases.The first one was liquid crystalline type 1,4-n-Hexyloxy benzoate-4-benzoic acid while the second one was conventional type of stationary phase PEG. Various aldehyde and ketone compounds with different functional groups were analyzed on the two columns in order to emphases the differences on their retention behaviors.In the range of the studied temperatures, 100-160ºC, it has been found that the chromatographic performance and the resolution of separation was significant in PEG column in comparison with the liquid crystalline column. The basic thermodynamic functions such as enthalpy, entropy and Gibbs energy for various compounds were calculated on the two columns.The results have exhibited the solubility on both columns occurred are not spontaneously because the values of Gibbs energy are positive while the values of entropy and enthalpy were negative.